HUMAN UROGENITAL MYIASIS CAUSED BY CHRYSOMYIA BEZZIANA - T.Jdalayer; M.Maleki; M.Moghtaderi (Tehran University of Medical Sciences, 1978)
Myiasis caused by the larvae of C.bezziana has been reported in man, cattle, cats, water buffalo, sheep, goats, horses, donkeys, dogs, camels and elephants from Asia and Africa. Although human infestation o with this parasite is commonly found in cattle-raising areas, cases of urogenital Myiasis are rarely reported. This is the first cases report of urogenital infestation with the larvae of C. bezziana in Iran